CodePlexProject Hosting for Open Source Software

2

Closed

Hi,

there is an issue,

If (-1)^3 = -1, then (-1)^(1/3) = -1 because (-1)*(-1)*(-1) = -1 and also for:

(-2)^3=-8, then (-8)^(1/3) must be = to -2, because (-2)*(-2)*(-2)=-8.

For pair exponents:

If n is pair then (-1)^n = 1

For odd exponents:

If n is odd then (-1)^n = -1

Regards

Ronny

there is an issue,

If (-1)^3 = -1, then (-1)^(1/3) = -1 because (-1)

(-2)^3=-8, then (-8)^(1/3) must be = to -2, because (-2)

For pair exponents:

If n is pair then (-1)^n = 1

For odd exponents:

If n is odd then (-1)^n = -1

Regards

Ronny

No files are attached

## comments

sys_27 wrote May 26, 2014 at 6:57 AM

sys_27 wrote May 26, 2014 at 7:17 AM